Nanotechnology in agriculture: A review of innovative utilization - Zamri, Nur Balqis (Malaysian NANO-An International Journal, 2023)
The escalating challenges posed by swift population growth, global climate change, and occurrences of disease outbreaks to ensure food security necessitate innovate agricultural improvement techniques. In this intricate milieu, nanotechnology, with its remarkable advancements, emerges as a potent avenue for enhancing sustainable agricultural practices. This review underscores the current landscape of nanotechnology in agriculture, highlighting the classification and synthesis of nanomaterials. Furthermore, insightful applications of nano-based products in agriculture are meticulously elucidated in term of advantages and risks possessed. Notably, the regulatory frameworks from different countries have been addressed to ensure the safety of consumers and the environment. However, despite its myriad benefits, nanotechnology is not exempt from limitations and potential negative consequences, which are explored in the final section of this review. Keywords: nanomaterials, agriculture, nano-based products, regulatory frameworks